Gene Turnover Contributes to the Evolutionary Adaptation of Acidithiobacillus caldus: Insights from Comparative Genomics - Zhang, Xian; Liu, Xueduan; He, Qiang; Dong, Weiling; Zhang, Xiaoxia; Fan, Fenliang; Peng, Deliang; Huang, Wenkun; Yin, Huaqun (Frontiers in Microbiology, 2016)
Acidithiobacillus caldus is an extremely acidophilic sulfur-oxidizer with specialized characteristics, such as tolerance to low pH and heavy metal resistance. To gain novel insights into its genetic complexity, we chosen six A. caldus strains for comparative survey. All strains analyzed in this study differ in geographic origins as well as in ecological preferences. Based on phylogenomic analysis, we clustered the six A. caldus strains isolated from various ecological niches into two groups: group 1 strains with smaller genomes and group 2 strains with larger genomes. We found no obvious intraspecific divergence with respect to predicted genes that are related to central metabolism and stress management strategies between these two groups. Although numerous highly homogeneous genes were observed, high genetic diversity was also detected. Preliminary inspection provided a first glimpse of the potential correlation between intraspecific diversity at the genome level and environmental variation, especially geochemical conditions. Evolutionary genetic analyses further showed evidence that the difference in environmental conditions might be a crucial factor to drive the divergent evolution of A. caldus species. We identified a diverse pool of mobile genetic elements including insertion sequences and genomic islands, which suggests a high frequency of genetic exchange in these harsh habitats. Comprehensive analysis revealed that gene gains and losses were both dominant evolutionary forces that directed the genomic diversification of A. caldus species. For instance, horizontal gene transfer and gene duplication events in group 2 strains might contribute to an increase in microbial DNA content and novel functions. Moreover, genomes undergo extensive changes in group 1 strains such as removal of potential non-functional DNA, which results in the formation of compact and streamlined genomes. Taken together, the findings presented herein show highly frequent gene turnover of A. caldus species that inhabit extremely acidic environments, and shed new light on the contribution of gene turnover to the evolutionary adaptation of acidophiles.